2017
DOI: 10.1162/artl_a_00223
|View full text |Cite
|
Sign up to set email alerts
|

Online Gait Learning for Modular Robots with Arbitrary Shapes and Sizes

Abstract: Abstract. This paper addresses a principal problem of in vivo evolution of modular multi-cellular robots. To evolve robot morphologies and controllers in real-space and real-time we need a generic learning mechanism that enables arbitrary modular shapes to obtain a suitable gait quickly after 'birth'. In this study we investigate a reinforcement learning method and conduct simulation experiments using robot morphologies with different size and complexity. The experiments give insights into the online dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Most of the mentioned research considers the off-line development of locomotive controllers, i.e., controller optimization as a separate phase before deployment intending to developing controllers that remain fixed once deployed. Weel et al (2017) considered on-line gait learning, where the controller is adapted to the robot's task environment during deployment. The experiments showed that spline-based controllers with the RL PoWER algorithm provide dynamic autonomous on-line gait learning capabilities.…”
Section: Lifetime Locomotion Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the mentioned research considers the off-line development of locomotive controllers, i.e., controller optimization as a separate phase before deployment intending to developing controllers that remain fixed once deployed. Weel et al (2017) considered on-line gait learning, where the controller is adapted to the robot's task environment during deployment. The experiments showed that spline-based controllers with the RL PoWER algorithm provide dynamic autonomous on-line gait learning capabilities.…”
Section: Lifetime Locomotion Learningmentioning
confidence: 99%
“…Therefore, we adopt a system architecture that does contain such a phase. This architecture, called the Triangle of Life, was introduced in Eiben et al (2013) and used in several experimental studies that addressed the task of gait learning (Rossi and Eiben, 2014;Jelisavcic et al, 2016;Weel et al, 2017). Note that the choice of the gait learning task is not arbitrary.…”
Section: Introductionmentioning
confidence: 99%
“…], [6]. The properties of this algorithm were investigated in comparison to HyperNEAT and Simulated Annealing [7], [19]. These studies have shown that RL PoWER is a superior method for on-line gait learning since it converges quickly to learn sufficiently good gaits in a short time.…”
Section: Related Workmentioning
confidence: 99%
“…Technically speaking, we are interested in a general gait learning algorithm that works for any given robot within the space of all possible morphologies constructible with the modules we use. Our algorithm of choice is the RL PoWER algorithm as proposed by Kober and Peters [6] and employed for gait learning in Roombots in our previous work [7].…”
Section: Introductionmentioning
confidence: 99%
“…23 Because of low cost, time consumption, and high precision of online learning for large-scale samples, online learning is applied to multiple fields, such as dynamic two categories, 24 vowel imitation learning, 25 and modular robots. 26 In this article, the smooth iterative online support tensor machine (SIOSTM) algorithm was developed by combining the two algorithms of linear SHTM and online stochastic gradient descent (OSGD). Using the tensor-type data as input, the characteristic parameters of the fault samples of the electric vehicle extension were extracted and the fault parameters were diagnosed.…”
Section: Introductionmentioning
confidence: 99%